(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we are concerned with the well-posedness and large time behavior of Cauchy problem for viscous Cahn-Hilliard-Oono system with chemotaxis in 3D whole space. By using the pure energy method, standard continuity arguments together with negative Sobolev norm estimates, one proves the global well-posedness and time decay estimates.